Synthesize and application of magnetic molecularly imprinted polymers (mag-MIPs) to extract 1-Aminopyrene from the human urine sample. Issue 5 (October 2021) - Nadali, Azam; Leili, Mostafa; Afkhami, Abbas; Bahrami, Abdolrahman; Karami, Manoochehr
Abstract: New magnetic molecularly imprinted polymers (mag-MIP) were developed for 1-Aminopyrene (1-Ap) detection in human urine samples. 1-Ap is a biomarker for exposure to the 1-Nitropyrenes (as a mutagenic compound) present in the particles emitted from various sources mainly the diesel engines. Fe3 O4 (as a magnetic core), TEOS, 1-Ap (as a template), MAA (as a functional monomer), EGDMA (as a cross-linker), and AIBN (as an initiator) were utilized for mag-MIP fabrication in the three-stage processes. Polymer characterization was performed using FTIR, SEM, TEM, and VSM analysis. HPLC-Fl equipment was used for 1-Ap detection. The recoveries and limit of detection were obtained 0.25 µg/ L and 87.2–95.7%, respectively. The results of the nonlinear isotherm and kinetics models had shown maximum adsorption capacity of 51 µg/mg for mag-MIP at relatively short equilibrium time of 30 min for 1-Ap, which was 2.9 times more than magnetic molecularly non-imprinted polymers (mag-NIP). A rapid magnetic separation (13.70 emu/g, 30 s) was observed for mag-MIP applications. Therefore, the present mag-MIP can be successfully used for 1-Ap extraction and detection. Graphical Abstract: ga1